To beat COVID, eating enough is not enough - Roy, Devesh; Sharma, Manika (Outlook Group, 2020)
While ensuring food and economic security for the poor is obviously a high priority, we cannot ignore the clear linkage between unhealthy diets and the severity of the pandemic.